EFFECT OF GROUP COUNSELING ON BREASTFEEDING SELF-EFFICACY AMONG NULLIPAROUS WOMEN ATTENDING TO HEALTH CENTERS IN HAMADAN, IRAN - Shobeiri, Fatemeh; Moradi Haghgoo, Somaieh; Khodakarami, Batool; Roshanaie, Ghodratolla (Journal of Postgraduate Medical Institute, 2019)
Objective: To determine the effect of group counseling on breastfeeding self-efficacy among nulliparous women in Hamadan City of Iran. Methodology: This project was a randomized clinical trial study. A total of 136 nulliparous women referring to health centers in Hamadan, Iran in 2017 who had got the minimum self-efficacy score were randomly divided into two experimental and control groups (n = 68). The data collection tool was a personal information questionnaire, Fax and Dennis Breastfeeding Self Efficacy Scale, which was filled out before and after the intervention. Data were analyzed by independent t-test, paired t-test and chi square using SPSS 21 software. Results: The findings showed that mean age was 24.8 ±4.9 in the experimental group and 23.8 ±4.8 in the control group, and the mean of the spouse's age in the experimental and control groups were 29.2 ±4.8 and 27.5 ±3.7, respectively. Most of the subjects in the experimental group (73.5%) had moderate self efficacy before the intervention and only 20.6% of the subjects had high or favorable self-efficacy. At the end of the study, 50% of the attendants earned average self efficacy and 50% earned high self efficacy. Conclusion: Group counseling among nulliparous women had a positive effect on the breastfeeding self-efficacy among them.